Growth factor loaded in situ photocrosslinkable poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/gelatin methacryloyl hybrid patch for diabetic wound healing - Robin Augustine (3976964) (2021)
Management of chronic diabetic ulcers remains as a major challenge in healthcare which requires extensive multidisciplinary approaches to ensure wound protection, management of excess wound exudates and promoting healing. Developing wound healing patches that can act as a protective barrier and support healing is highly needed to manage chronic diabetic ulcers. In order to boost the wound healing potential of patch material, bioactive agents such as growth factors can be used. Porous membranes made of nanofibers generated using electrospinning have potential for application as wound coverage matrices. However, electrospun membranes produced from several biodegradable polymers are hydrophobic and cannot manage the excess exudates produced by chronic wounds. Gelatin-methacryloyl (GelMA) hydrogels absorb excess exudates and provide an optimal biological environment for the healing wound. Epidermal growth factor (EGF) promotes cell migration, angiogenesis and overall wound healing. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) membranes provide microbial, thermal and mechanical barrier properties to the wound healing patch. Herein, we developed a biodegradable polymeric patch based on the combination of mechanically stable electrospun PHBV, GelMA hydrogel and EGF for promoting diabetic wound healing. In vitro and in vivo studies were carried out to evaluate the effect of developed patches on cell proliferation, cell migration, angiogenesis and wound healing. Our results showed that EGF loaded patches can promote the migration and proliferation of multiple types of cells (keratinocytes, fibroblasts and endothelial cells) and enhance angiogenesis. In situ development of the patch and subsequent in vivo wound healing study in diabetic rats showed that EGF loaded patches provide rapid healing compared to control wounds. Interestingly, 100 ng EGF per cm2 of the patches was enough to provide favourable cellular response, angiogenesis and rapid diabetic wound healing. Overall results indicate that EGF loaded PHBV-GelMA hybrid patch could be a promising approach to promote diabetic wound healing. Other Information Published in: Materials Science and Engineering: C License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.msec.2020.111519